Planning for Degrowth: How artificial intelligence and Big Data revitalize the debate on democratic economic planning - Leo Schlichter (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2024)
The Degrowth movement advocates a radical shift from our capitalist economic system to one based on human needs, planetary boundaries, and economic democracy. The literature, however, often neglects detailing the concrete coordination mechanisms of a Degrowth economy. This paper addresses this gap by proposing democratic economic planning as a potential solution. I delve into historical and contemporary planning debates, examining practical examples and proposals that leverage artificial intelligence and cybernetics for democratic economic planning. I argue that models such as participatory economics (Parecon) or Daniel Saros's planning model align well with Degrowth principles, forming a foundation for further exploration. Effective economic planning requires democratic participation, free information flow, and safeguards against power abuse. Still, open questions on money, trade, democratic institutions, and privacy protection require further investigation.
Keywords: B50; O49; P11; P21; P40; 330; Degrowth; economic democracy; economic planning; participatory economics